Assessment of Performance Parameters of a Series of Five ‘Historical’ Cricket Bat Designs - Bull,AMJ; Eftaxiopoulou,T; Persad,L (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
The performance of five different bat designs, from different eras spanning from 1905 to 2013, was assessed to addressthe question whether the changes in bat design over the years have resulted in a performance advantage to the batsman.Moment of inertia and ‘freely suspended’ vibration analysis tests were conducted, as these physical properties have beendirectly associated with rebound characteristics of the bats. Results showed that changes in the blade’s profile such asdistribution of the blade’s weight along the edges and closer to the toe have resulted in a clear performance advantageof the newest bats in comparison with older designs. These results add to the weight of evidence in cricket that thegame has changed to the benefit of the batsman and additional changes to bat design are conceivable as modern engineeringtools are applied to further optimise performance.